A comparison of serum potassium level between high dose and low dose of Succinylcholine - Yadav, RK; Majhi, PC; Tiwari, D (Journal of College of Medical Sciences-Nepal, 2014)
Aims: Succinylcholine is a depolarizing type of neuromuscular blocking drug. Aim of this study is to evaluate and compare serum potassium level with upper dose limit of succinylcholine (1.5mg/kg), which is used normally in anesthetic practice with low dose of succinylcholine (0.5mg/kg). Materials and methods: A total of 100 patients attending for elective surgery in College of Medical Sciences -Teaching Hospital( CMSTH)), Bharatpur, Chitwan, Nepal were studied. Two blood samples were collected, one before surgery and another at 4 min after injection of succinylcholine and send to central lab for estimation of serum potassium level. Result: The serum potassium levels recorded during the study showed that there were neither significant differences observed within the groups nor was there any difference between the groups. Conclusion: In absence of pathological conditions related to raised serum potassium level, both high and low doses of succinylcholine can be used safely as there is no statistically significant differences in serum potassium level between high and low dose of succinylcholine. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-1, 19-22 DOI: http://dx.doi.org/10.3126/jcmsn.v9i1.9669